A leanness assessment methodology based on neutrosophic DEMATEL - AĞLAN GÖKLER, CANAN; KILIÇ, HÜSEYİN SELÇUK (ELSEVIER SCI LTD, 2021)
Lean systems which provide the elimination of waste and increase productivity in both manufacturing and service systems are highly desired by the companies. Designing a lean system requires enormous amount of efforts and is time consuming unless the right steps are followed. The first step of lean implementation is the assessment of leanness which determines the status quo of the existing system with respect to leanness. In searching of a comprehensive evaluation method, this study aims to propose a leanness assessment methodology which is able to aid company's lean transformation. This study mainly differs from the existing studies by taking into account a wide range of lean indicators with a comprehensively designed questionnaire and evaluating leanness via neutrosophic DEMATEL (The Decision Making Trial and Evaluation Laboratory) based scoring structure. The proposed methodology is applied in three companies. Moreover, sensitivity analysis concerning metrics and comparison with classic DEMATEL are performed.
Keywords: Lean production; Leanness assessment; Leanness scoring; Neutrosophic DEMATEL; Leanness questionnaire; MANUFACTURING SYSTEMS; SUPPLY CHAIN; PERFORMANCE EVALUATION; FUZZY-LOGIC; MODEL; IMPLEMENTATION; FRAMEWORK; ANP; LEVEL; INDEX